(untitled) (Bangladesh Journal of Infectious Diseases, 2024)
Background: Clinical features of COVID-19 include features directly related to infection, but the clinical spectrum of COVID-19 is also a consequence of the spectrum of the immune responses to the. Since the pandemic in 2020, many studies and observations were made about certain immunological manifestations and relevant physical signs including strawberry tongue. Objective: The purpose of the present study was to assess the prevalence of the strawberry tongue in patients with PCR positive COVID-19 infection and to determine the association between this finding and other manifestations of the disease. Methodology: This study was a prospective case control study, fifty patients who attended the outpatient internal medicine clinic in the period from June 2023 to July 2023 and tested positive for COVID-19 were collected. The presence of strawberry tongue was documented along with other clinical and laboratory manifestations. The results were compared to fifty cases who presented with acute febrile illness and tested negative for COVID-19. The results were analyzed using SPSS 23 and P value less than 0.05 was considered statistically significant. Results: The study revealed that 78.0% (30 patients) of PCR positive patients had strawberry tongue, this sign appeared earlier in the course of the illness (the first two days). About 80.0% of patients with strawberry tongue sign had vomiting and diarrhea (60.0% of the overall population study). Patients with strawberry tongue had excellent response to systemic corticosteroids in the form of improved fever, fatigue and gastrointestinal symptoms so the presence of this sign may be an indirect clue for early initiation of steroid therapy. Conclusion: In conclusion, a large proportion of patients with fever and positive COVID-19 PCR test have strawberry tongue. It is more common in young age group and it is significantly associated with the occurrence of vomiting and diarrhea. Bangladesh Journal of Infectious Diseases, June 2024;11(1):9-15